RIFM fragrance ingredient safety assessment, (+-)-ethyl 3-mercapto-2-methylbutanoate, CAS Registry Number 888021-82-7. (March 2023) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Cancellieri, M.A.; Chon, H.; Dagli, M.L.; Dekant, W.; Deodhar, C.; Fryer, A.D.; Jones, L.; et al.
Highlights: (+-)-Ethyl 3-mercapto-2-methylbutanoate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.